The Use of Technology in English Language Learning: A Case Study of E-Learning Application Implementation - Zainuddin; Hamdani, Beny (Universitas Terbuka, 2024)
A case study of the implementation of an e-learning application is the focus of this research project, Utilizing Technology in English Language Learning. In this study, a systematic literature review was the strategy employed. Strategies for collecting data accompanied by documentation from Google Scholar. Data analysis combined with a critical evaluation. It is very possible to improve the efficiency and accessibility of education by implementing e-learning apps in English language instruction. This case study incorporates interactive and flexible technology as a technique for integrating English language learning materials. Students are thus more involved and engaged in the learning process because they have access to learning resources at all times and locations. More effectively tracking and evaluating student progress is also made possible by e-learning systems. However, the success of this implementation relies heavily on good design, user training, and adequate technical support to maximize the potential of learning English through this technology.